Relapse following orthodontic rotation of teeth in dogs - Lovatt Russell; Goonewardene Mithran; Tennant Marc (Sciendo, 2023)
Rotation of recently emerged or an emerging tooth before the supracrestal fibres have become established may result in less rotational relapse.